Malta : Financial Sector Assessment Program-Technical Note-Macroprudential Policy Framework and Tools. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note evaluates the domestic macroprudential policy framework in Malta and provides recommendations to strengthen it. It assesses: the domestic institutional arrangements; the systemic risk monitoring framework; and the macroprudential policy toolkit. It also assesses current financial vulnerabilities in Malta to develop specific policy recommendations. The paper also reviews the current domestic institutional arrangements and provides recommendations and discusses the existing systemic risk monitoring framework and provides options to enhance it further. The legal backing of inter-agency coordination could be further strengthened. The report highlights that the planned introduction of borrower-based measures is a welcome step to proactively address a build-up of vulnerabilities in the housing and household sectors. There is scope to refine the design of the planned borrower-based measures to reduce uncertainty over policy effects. The Central Bank of Malta plans to introduce borrower-based measures to proactively address the potential build-up of vulnerabilities in the housing and household sectors.